Putting Theory to Practice: Applying Cognitive Load Theory to Resident Medical Education. Issue 2 (February 2022) - Cramer, Natan; Zuckerbraun, Noel Spears; Puller, Justin; Furtado, Andre D.; Deb, Arjamon; Dorfsman, Michele L.; Siripong, Nalyn; Christie, Meghan; Tavarez, Melissa M.
Abstract : Objective: We built 2 versions of an asynchronous pediatric orthopedic educational intervention for emergency medicine residents and sought to compare the two. We hypothesized that the version incorporating more instructional scaffolding in the form of a cognitive aid (CA) would optimize germane cognitive load for our target novice learners and result in higher test scores. Methods: Learners were block randomized to either a "CA" or "non-CA" arm, each containing a random set of 18 modules. The CA arm incorporated an orthopedic fracture classification chart embedded within the diagnostic questions to guide the learner in forming a diagnosis. The non-CA arm was designed with more active learning as the classification chart was provided only after each diagnostic answer submission. For both arms, the final 6 modules completed per learner were scored. Learners also completed a perceived cognitive load assessment tool measured on a 10-point Likert scale. Results: Learners in the non-CA arm had a mean total score on the testing modules of 33% correct compared with a mean total score of 44% correct for learners in the CA arm (mean difference, 11; 95% confidence interval, 4%–19%, P = 0.005). There was a trend for the CA arm to have lower perceived overall cognitive load scores; however, this did not reach statistical significance. Conclusions: Emergency medicine residents performed better after completing the CA version of our educational intervention. Applying cognitive load theory to an educational intervention may increase its success among target learners. Abstract : Supplemental digital content is available in the text.